2015
DOI: 10.1111/febs.13521
|View full text |Cite
|
Sign up to set email alerts
|

TheTCP1γ subunit ofLeishmania donovaniforms a biologically active homo‐oligomeric complex

Abstract: Chaperonins are a class of molecular chaperons that encapsulate nascent or stress‐denatured proteins and assist their intracellular assembly and folding in an ATP‐dependent manner. The ubiquitous eukaryotic chaperonin, TCP1 ring complex is a hetero‐oligomeric complex comprising two rings, each formed of eight subunits that may have distinct substrate recognition and ATP hydrolysis properties. In Leishmania, only the TCP1γ subunit has been cloned and characterized. It exhibited differential expression at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…amazonensis promastigotes in culture. The exact function of the TCP complex is not known in Leishmania spp., although it has been suggested that the TCP1γ subunit may participate in maintaining the structural dynamics of the cytoskeleton [ 29 ]. Changes in cell morphology throughout promastigote differentiation and flagellar movement demand continuous re-organization of the cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…amazonensis promastigotes in culture. The exact function of the TCP complex is not known in Leishmania spp., although it has been suggested that the TCP1γ subunit may participate in maintaining the structural dynamics of the cytoskeleton [ 29 ]. Changes in cell morphology throughout promastigote differentiation and flagellar movement demand continuous re-organization of the cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the heterohexadecamer form, the TRiC subunits can function as monomers (Brackley & Grantham, ; Liou & Willison, ; Tam et al . , ), other microcomplexes with two or more subunits (Liou & Willison, ), homo‐oligomers (Bhaskar, Mitra, Kuldeep, Siddiqi, & Goyal, ), and can also form homohexadecamers (Sergeeva et al . , ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the heterohexadecamer form, the TRiC subunits can function as monomers (Brackley & Grantham, 2010;Liou & Willison, 1997;Tam et al, 2006), other microcomplexes with two or more subunits (Liou & Willison, 1997), homo-oligomers (Bhaskar, Mitra, Kuldeep, Siddiqi, & Goyal, 2015), and can also form homohexadecamers (Sergeeva et al, 2013). In our study, we observed monomeric forms and micro-complexes for all subunits examined (Figures 3-5) and notably the higher molecular weight complexes observed for the TRiC-θ subunit were different to those of other subunits (Figure 4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Co‐immunoprecipitation and western blot analysis of the γ subunit of the chaperonin containing T‐complex protein (TCP) complex of L. donovani promastigotes revealed high molecular weight complexes involved in protein folding. In addition, the interaction of the TCPγ with tubulin and actin suggested a structural role in the parasite cytoskeleton …”
Section: Proteomics Approaches In Leishmaniamentioning
confidence: 99%
“…In addition, the interaction of the TCPγ with tubulin and actin suggested a structural role in the parasite cytoskeleton. [74] An important complex required for the degradation and recycling of cytosolic proteins was demonstrated in L. major by MS analysis. [75] The autophagy-related protein 5 to 12 (ATG5-ATG12) complex is a key component of autophagy, and the identification of peptides from ATG5 and ATG12 in a 70 kDa band following analysis by MS confirmed the existence of this protein complex in Leishmania.…”
Section: Protein Complexes In Leishmaniamentioning
confidence: 99%